Campylobacter bacteraemia: 16 years of experience in a single centre. Issue 11 (1st December 2016) - Hussein, Khetam; Raz-Pasteur, Ayelet; Shachor-Meyouhas, Yael; Geffen, Yuval; Oren, Ilana; Paul, Mical; Kassis, Imad
Abstract: Background: Campylobacter bacteraemia (CB) is rare and usually occurs in immune-compromised patients. In this study we examined the incidence and epidemiology of CB in one institution over 15.5 years. Methods: The medical records of all the consecutive patients with CB admitted to our hospital from 2000 to 2015 were retrospectively reviewed. Clinical characteristics, microbiologic and outcome data were collected. Results: During the study period, 65 patients with CB were identified. The majority of the patients were middle aged and immune-compromised. Campylobacter jejuni was the most commonly identified species (33/47, 70%). The main underlying conditions were haematological malignancies (43%) and chronic liver disease (14%). Fifty-seven percent of the patients were receiving immunosuppressive therapy at the time of bacteraemia. The most common presenting symptoms were fever (85%), diarrhoea (40%), abdominal pain (40%), and nausea and vomiting (40%). Of the isolates tested, 97% were susceptible to macrolides, and only 35% were susceptible to quinolones. Susceptibility to quinolones decreased over the years. Most patients did not receive adequate empiric antibiotic treatment (81.5%) and about 20% never received directed therapy. Mortality and relapse rates were low (5% each). There was no association between adequate empirical or definitive antibiotic therapy and adverse outcomes. Conclusion: The main predisposing factor for Campylobacter bacteraemia in our cohort was immunosuppression. Prognosis was generally favourable regardless of appropriateness of antibiotic therapy.